2004
DOI: 10.1117/12.530239
|View full text |Cite
|
Sign up to set email alerts
|

Laser microjoining of dissimilar and biocompatible materials

Abstract: Micro-joining and hermetic sealing of dissimilar and biocompatible materials is a critical issue for a broad spectrum of products such as micro-electronics, micro-optical and biomedical products and devices. Today, biocompatible titanium is widely applied as a material for orthopedic implants as well as for the encapsulation of implantable devices such as pacemakers, defibrillators, and neural stimulator devices. Laser joining is the process of choice to hermetically seal such devices. Laser joining is a conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The group of metal materials includes titanium, platinum, gold and stainless. Non-metals play an even more important role based on their biocompatibility include glass, sapphire, silicon and polymers, as be pointed out by Bauer et al (2004).…”
Section: Introductionmentioning
confidence: 97%
“…The group of metal materials includes titanium, platinum, gold and stainless. Non-metals play an even more important role based on their biocompatibility include glass, sapphire, silicon and polymers, as be pointed out by Bauer et al (2004).…”
Section: Introductionmentioning
confidence: 97%
“…Transmission laser joining at micro scale has not been studied well yet. We studied the laser microjoining of dissimilar and biocompatible materials using both diode and fiber lasers and observed that the joining of glass to silicon and polymer to metal is very promising [13]. As part of the study, we developed an experimental setup (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of biomedical implants and their encapsulation, the laser bonding technique has potential to become a unique joining process for its high precision and biocompatibility property, as no additional adhesive materials are required in this case. Our research group in collaboration with Fraunhofer USA has been studying the applicability of laser fabrication process in joining dissimilar and biocompatible materials [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A transmission joining configuration [7] was used in which a clamping pressure of 200 MPa was used for the fabrication of the samples examined in this work. The laser beam with a total power of 1.0 W was loosely focused on the Ti surface to a spot with diameter of 300gam.…”
Section: Samples Preparation and Experimental Conditionsmentioning
confidence: 99%
“…The feasibility of laser joining PI to titanium and PI to titanium-coated glass has been investigated, and ranges of processing parameters that permit successful joining have been identified [7]. In order to understand the influence of the laser fabrication conditions on the joint quality and stability, we examined laser-fabricated joints between PI and titanium-coated borosilicate glass (BSG) in tensile mechanical failure tests and by optical microscopy, X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%